UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI MENGGUNAKAN METODE PAIKEM GEMBROT - Nurdiansyah, Sinta; Darifah, Udung Hari; Selamet, Selamet (Bestari, 2019)
This classroom action research article produces several conclusions: First, a well-planned and well-organized PAI learning is neatly to help the teacher carry out the Learning process using the PAIKEM Gembrot method in PAI subjects at Sukajaya State Primary School 4, Rajadesa District, Ciamis. Secondly, the use of the PAIKEM Gembrot method in the PAI subjects at State Elementary School 4 Sukajaya, Rajadesa District can increase the activities of teachers and students in the learning process. The results before the study got a score of 35% in the first cycle 60%, and the second cycle 85%. Third, the use of the PAIKEM Gembrot method in the PAI subjects at State Elementary School 4 Sukajaya, Rajadesa sub-district can increase students' learning motivation